Leveraging socio-religious capital: The Islamic philosophical framework for SDG 6 achievement in Indonesia - Rafiqah Dwi Rahmah (Islamic perspective on Communication and Psychology, 2026)
Background: Goal 6 of the SDGs aims to ensure the availability and sustainability of water and sanitation services for all by 2030, but its fulfilment is severely threatened in Indonesia due to resource mismanagement and weak social accountability. Although water is an important resource with clear conservation instructions in Islamic Religious Education (PAI), the gap between technical rules and ethical compliance persists. Therefore, this study aims designed to explore a convergent philosophy between PAI values and goals in 6 of SDG to develop a novel model for best-practice in water conservation Methods: This study uses a systematic literature review approach by collecting data using Publish or Perish software on the Scopus and Google Scholar databases, and then the findings are analyzed using PRISMA 2020 and thematic analysis with qualitative software Nvivo 12. Findings: The findings of ecological implementation in Indonesia are classified into 7 groups, namely ecology (traditional), eco-campus, eco-economic, eco-mosque, eco-pesantren, eco-riparian, and eco-technology. The seven groups are a form or form of environmental awareness through the values of Islamic religious education and hygiene. Conclusion: The research provides a new theoretical lens, the PAI K3 Model of three pillars: Kesederhanaan (Resource Efficiency), Kolaborasi (Communal Resilience), and Keadilan (Equity in Access). These values are broken down systematically with an Ontology-Epistemology-Axiology paradigm. Results demonstrate that the PAI ethos is vibrantly being institutionalized – particularly in Eco-Pesantren and universities – pioneering novel water conservation practices inclusive of technology tools. Novelty/Originality of this article: The novelty and contribution of this paper are the PAI K3 Model, which translates PAI's socio-religious capital into an applicable tool. This model serves as a theological–ecological hermeneutic that grounds the moral imperative of hifẓ al-nafs (Ontology) to legal obligation (Axiology) and aspires to make resource conservation efforts both successful and socially just. This structure is key to Islamic convictions for fulfilling SDG 6, not with technical prowess but through developing sustainable moral compliance in Muslim-majority countries.